Teori Belajar Populer(Pendidikan Karakter Cerdas, Quantum Learning, Accelerated Learning, Active Learning, Hypno Teaching): Array - Iqbal Arrahman; Neviyarni; Herman Nirwana (Citra Dharma Cindekia, 2022)
Character education includes elements of knowledge (cognitive), sentiment (feelings), and actions. Character development is character development plus. (action). Thomas Lickona argues that character education will not be effective without these three components. A child will develop emotional intelligence through consistent and methodical character education. A comprehensive technique called quantum learning combines rapid classroom implementation with educational theory. The best educational elements are incorporated into the whole through the use of a research-based approach, which gives the curriculum more importance and relevance in students' lives. Accelerated learning is a teaching method intended to stimulate students' cognitive abilities and make learning more enjoyable and efficient. Active learning encourages students to participate in the learning process. When students participate actively in their learning, it means they are in control of the process. They actively use their brains to come up with main ideas for topics, solve problems, or apply what they just learned to real problems. Subject content is presented through subconscious language in